A Supramolecularly Activated Radical Cation for Accelerated Catalytic Oxidation. Issue 31 (6th June 2016) - Jiao, Yang; Li, Wan‐Lu; Xu, Jiang‐Fei; Wang, Guangtong; Li, Jun; Wang, Zhiqiang; Zhang, Xi
Abstract: Tuning the activity of radicals is crucial for radical reactions and radical‐based materials. Herein, we report a supramolecular strategy to accelerate the Fenton reaction through the construction of supramolecularly activated radical cations. As a proof of the concept, cucurbit[7]uril (CB[7]) was introduced, through host–guest interactions, onto each side of a derivative of 1, 4‐diketopyrrolo[3, 4‐ c ]pyrrole (DPP), a model dye for Fenton oxidation. The DPP radical cation, the key intermediate in the oxidation process, was activated by the electrostatically negative carbonyl groups of CB[7]. The activation induced a drastic decrease in the apparent activation energy and greatly increased the reaction rate. This facile supramolecular strategy is a promising method for promoting radical reactions. It may also open up a new route for the catalytic oxidation of organic pollutants for water purification and widen the realm of supramolecular catalysis. Abstract : Acceleration to dye for : In the Fenton oxidation of a 1, 4‐diketopyrrolo[3, 4‐ c ]pyrrole dye (see scheme), the key electron‐deficient radical‐cation intermediate was activated by host–guest interactions with electrostatically negative cucurbit[7]uril. A drastic decrease in the apparent activation energy of the transformation, and thus a remarkable improvement in the reaction rate, was observed upon the formation of the supramolecular complex.